2021
DOI: 10.3393/ac.2020.03.16
|View full text |Cite
|
Sign up to set email alerts
|

The Long-term Effect of Standardized Anal Dilatation for Chronic Anal Fissure on Anal Continence

Abstract: Purpose: For the past several decades, internal anal sphincterotomy has generally been considered to be the standard operation for an anal fissure. However, wound complications inherent in this operation forced surgeons to look for an alternative form of treatment. The aim of our study was to evaluate the long term outcome of anal dilatation for chronic anal fissure, especially possible negative impact on anal sphincter function.Methods: The study was approved by the Local Institutional Review Board and given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Both the techniques have been found to result is quick pain relief and high ulcer healing rate. Hartikainen [4] Pandit [6] reported that there was no significant age difference between the two groups as regard age and sex, Yucel [8] found no significant difference between gender and the age distributions of the patient and Pinsk [9] also showed that there were no significantly different between the groups as regard age and sex. Kiyak [5] showed that there were 68 (52.7%) female and 61 (47.3%) male patients.…”
Section: Discussionmentioning
confidence: 99%
“…Both the techniques have been found to result is quick pain relief and high ulcer healing rate. Hartikainen [4] Pandit [6] reported that there was no significant age difference between the two groups as regard age and sex, Yucel [8] found no significant difference between gender and the age distributions of the patient and Pinsk [9] also showed that there were no significantly different between the groups as regard age and sex. Kiyak [5] showed that there were 68 (52.7%) female and 61 (47.3%) male patients.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory bowel disease and irritable bowel syndrome characterized mostly by diarrhea are risk factors for FI. However, any GI condition that causes frequent bowel movements or a change in bowel habits can lead to FI [17]. And the structural causes of FI are obstetric injuries [18], anorectal surgery [19,20], rectal prolapse [21], and anal intercourse [22].…”
Section: Definition and Etiology Of Fecal Incontinencementioning
confidence: 99%
“…For these reasons, less traumatic, precise, measurable, and reproducible techniques of anal dilatation were recently designed and introduced into practice: balloon dilatation and staged dilatation showed healing rates superimposable to those obtained after internal sphincterotomy, with complication and incontinence rates near zero [309][310][311][312][313][314]. These results were recently confirmed in a long-term follow-up study [315]. Unfortunately, all the studies cited above are mainly focused on chronic anal fissures.…”
Section: Pain Control (See Question 7d)mentioning
confidence: 99%